Labyrinth - Mosse, Kate. (London : Orion, 2006)
Two women separetedby eight centuries, become caught up in the same mystery when volunteer archaeologist Alice Tanner, working in a cave near Carrassone, stumbles upon two skeletons, and a stone ring engraved with a labyrinth which had been entrusted to Alais, the daughter of one of the appointed guardians of the Holy Grail, in 1209 on the eve of the invasion by French Crusaders.
Winner Richard Judy's Book club- British Book Award.
Keywords: Excavations (Archaeology) -- Fiction; Albigenses -- Fiction; France, Southwest -- Fiction; Time travel -- Fiction; Volunters -- Fiction